2022
DOI: 10.2166/wcc.2022.161
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on groundwater recharge and salinity distribution in the Vientiane basin, Lao PDR

Abstract: Groundwater is widely used for domestic, agricultural, and industrial purposes in the Vientiane basin. The trend of groundwater use is increasing but the usage of the mentioned groundwater is without proper study and monitoring. Six climatic scenarios from three General Circulation Models (GCMs) under Representative Concentration Pathways (RCPs) 4.5 and 8.5 were used to project rainfall and temperature in the future (2021–2050) periods. The numerical models HELP3, MODFLOW, and MT3D were used for groundwater re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…It may be observed that several past studies used projected climate data to estimate recharge and applied it in numerical groundwater models to estimate changes in groundwater levels and fluxes (Reinecke et al, 2021;Soundala and Saraphirom, 2022). Depending on the complexity of the recharge models, they use computationally complex solution of Richard's equation or simpler approaches like UZF1 or Hydrus 1D coupled to MODFLOW in which 1D solution of Richard's equation was used.…”
Section: Introductionmentioning
confidence: 99%
“…It may be observed that several past studies used projected climate data to estimate recharge and applied it in numerical groundwater models to estimate changes in groundwater levels and fluxes (Reinecke et al, 2021;Soundala and Saraphirom, 2022). Depending on the complexity of the recharge models, they use computationally complex solution of Richard's equation or simpler approaches like UZF1 or Hydrus 1D coupled to MODFLOW in which 1D solution of Richard's equation was used.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, the state of the lake can be seen as an indicator of the processes occurring in and around the lake, which are influenced by both human actions and climate [4]. Climate change is a global phenomenon, but its effects are felt regionally and locally [5]. The variability of lake ecosystems can be monitored by a continuous monitoring system, which for a number of reasons, both economic and geographical, is not feasible, and monitoring networks are in decline worldwide [6].…”
Section: Introductionmentioning
confidence: 99%